2023
DOI: 10.3390/su15032471
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Determine the Relationship between Air Pollution and the Real Estate Market in 2010–2020 in Gdańsk Using GLM and GRM Statistical Models

Abstract: World economic development, technological progress, and irrational exploitation of natural resources have intensified the negative effects of economic activity, which causes more attention to be paid to environmental pollution and the deterioration of the standard of living. Therefore, over the past few years, the concept of sustainable development has experienced a period of increased interest, accompanied by changes in the attitudes and expectations of all market participants. The article attempts to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Hedonic pricing models establish a link between the price of a market product and its characteristics, often employed to analyze the impact of environmental goods, sea access, or open space on the real estate market (Liebelt et al, 2018;Czechowski et al, 2023).…”
Section: Key Theoretical Conceptsmentioning
confidence: 99%
“…Hedonic pricing models establish a link between the price of a market product and its characteristics, often employed to analyze the impact of environmental goods, sea access, or open space on the real estate market (Liebelt et al, 2018;Czechowski et al, 2023).…”
Section: Key Theoretical Conceptsmentioning
confidence: 99%
“…Ordinary linear regression (OLS) was used to determine the linear relationship between influencing factors and PM 2.5 . Due to the fact that simple OLS cannot accurately explore the relationship between various factors and PM 2.5 , scholars have started to use methods such as logistic regression [12] and multiple linear regression [13,14]. With the deepening of research, it has been found that the spatial distribution of various factors can also affect the concentration of PM 2.5 , so Geographically Weighted Regression (GWR) has been introduced.…”
Section: Introductionmentioning
confidence: 99%